NEW RULES ON BRAZIL / US COOPERATION, BETWEEN THE FRUSTRATED PRODUCTION OF RENEWABLE FUELS AND THE CHALLENGES OF THE BIO-ECONOMY1 (2006-2018) - Yang, Antonio; Almeida, Wilson (Novos Estudos Jurídicos, 2019)
The industry of the 21st Century will be totally different from the one we experienced in the 19th and 20th centuries. It will be technology-intensive and energy-wise clean. The industry of the 21st century should be biodegradable and sustainable. Instead of transforming only products and raw materials it must transform the human beings. Brazilian agriculture with its technological advances and sophisticated production may be an important partner of the United States to create a new biological industry for the 21st Century. Brazil is the world’s leading producer of cotton, orange juice, chicken, beef, sugar, ethanol, biodiesel, soy, corn, among others. Brazil has the latest technology to genetically modify plants and animals. The United States is the world’s largest producer of many of the state-of-the-art technology products. Cooperation between the two countries in terms of genetic improvement of plants and animals has lasted for more than 40 years. Now, the next challenge is to invent a new industry and a new economy that can face the challenges ahead. These are some of the key gates to the bioeconomy.